2011
DOI: 10.1007/s10661-011-2041-7
|View full text |Cite
|
Sign up to set email alerts
|

Mercury concentration in the muscle of seven fish species from Chagan Lake, Northeast China

Abstract: Chagan Lake is located downstream of the Second Songhua River basin in Northeast China. It is one of the top ten inland freshwater lakes, and an important aquatic farm in China. The lake has been receiving large amounts (currently at 1.5 × 10(8) m(3)/a) of water from the river since 1984. This would pose a threat to the aquatic system of the lake because the river was seriously polluted with mercury in 1970s-1980s. The current study is the first to report the total mercury concentrations in fish found in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…Total length and species were negatively correlated to mercury levels in tilapia and muscle of the two fish species (Table 3 ). These results are in line with Zhu et al ( 2012 ) who looked at china fish species and found that age in addition to weight and length predicted mercury levels in fish muscle. The present study raises the possibility that large sized fish possessed more Mercury in Nile perch muscle (Sackett, Cope, Rice, & Aday, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Total length and species were negatively correlated to mercury levels in tilapia and muscle of the two fish species (Table 3 ). These results are in line with Zhu et al ( 2012 ) who looked at china fish species and found that age in addition to weight and length predicted mercury levels in fish muscle. The present study raises the possibility that large sized fish possessed more Mercury in Nile perch muscle (Sackett, Cope, Rice, & Aday, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…Some researchers believe that there is no difference in accumulation of mercury based on whether the fish is carnivorous or omnivorous, (Bidone, Castilhos, Santos, Souza, & Lacerda, 1997 ) while others have established a clear pattern of bioaccumulation of mercury in fish i.e. carnivorous fish have higher levels than the herbivorous and omnivorous fish a pointer towards the nutrition role in heavy metal toxicity (Zhu, Yan, Wang, & Pan, 2012 ). Looking now at the accumulation levels of mercury in the different parts of the fish i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Choice of the oral reference dose is critical in determining the health risks the vulnerable community is exposed to i.e. use of the general population or vulnerable population oral reference dose (Zhu et al, 2012 ). The results of this study reveal health risk when HQs were computed for the vulnerable population in the community.…”
Section: Discussionmentioning
confidence: 99%
“…To date several studies have used the levels of Mercury in the different fish species and fish parts to estimate the risk for humans and involves hazard ratios, acceptable risk levels, exposure levels, PTWI and transferable factor (Burger & Gochfeld, 2005 ; Sidhu, 2003 ; Tang et al, 2009 ; Zhu, Yan, Wang, & Pan, 2012 ). One of the shortfalls of these studies is the generalization of the risk across age groups and failure to extrapolate the risk to the Disability Adjusted Life Years (DALYs) accrued; a gap the current work is going to fill for the fishing communities in the Lake Albert.…”
Section: Introductionmentioning
confidence: 99%
“…El ambiente acuático está normalmente expuesto a una gran cantidad de tóxicos, consecuencia de intervenciones antropogénicas incluyendo la contaminación por residuos industriales (Acherman 2007), fumigación con herbicidas organofosforados como glifosato (Ramírez-Duarte et al 2008 y contaminación con metales pesados como el mercurio (Marrugo-Negrete et al 2008, zhu et al 2012.…”
Section: Introductionunclassified